2017
DOI: 10.3390/resources6040058
|View full text |Cite
|
Sign up to set email alerts
|

Biomethane: A Renewable Resource as Vehicle Fuel

Abstract: Abstract:The European Union (EU) has set a mandatory target for renewable fuels of 10% for each member state by 2020. Biomethane is a renewable energy representing an alternative to the use of fossil fuels in the transport sector. This resource is a solution to reach this target. Furthermore, it contributes to reducing carbon dioxide emissions, gives social benefits and increases the security supply. Sustainability is reached also when the economic opportunities are verified. This work studies the profitabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 27 publications
0
31
0
Order By: Relevance
“…The economic systems of the EU states are directly influenced by the energy policy at the EU level. The European energy system should respond to climate change challenges and support the achievement of sustainable growth in the EU member States [9]. The EU countries with higher GDP succeeded in making progress in production and utilization of renewable energies as higher economic development level provides more financial resources and opportunities to invest in new renewable energy technologies also taking into account geographical conditions of these countries [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The economic systems of the EU states are directly influenced by the energy policy at the EU level. The European energy system should respond to climate change challenges and support the achievement of sustainable growth in the EU member States [9]. The EU countries with higher GDP succeeded in making progress in production and utilization of renewable energies as higher economic development level provides more financial resources and opportunities to invest in new renewable energy technologies also taking into account geographical conditions of these countries [9].…”
Section: Introductionmentioning
confidence: 99%
“…The European energy system should respond to climate change challenges and support the achievement of sustainable growth in the EU member States [9]. The EU countries with higher GDP succeeded in making progress in production and utilization of renewable energies as higher economic development level provides more financial resources and opportunities to invest in new renewable energy technologies also taking into account geographical conditions of these countries [9]. Another possible explanation would be the fact that in the EU developed Member States the transition from fossil fuels to renewable energy sources is encouraged by well-developed national legislative frameworks and strong institutions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biomethane is currently emerging as one viable solution for the heavy-duty transport sector [10][11][12], with comprehensive reviews of its benefits and constraints [13,14], and of the required heavy-duty vehicle fleet [15]. The European biomethane market comprises 90% of the global supply [16] and has grown seven-fold since 2000 [17]. Production can be doubled by 2030 [8,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…In the past, several research studies reported the environmental and economic benefits of using CBM as transport fuel [11][12][13][14]. Importantly, CBM as transportation fuel reduces environmental externality costs [12] and economically incentivize operation of public transportation [15]. However, the potential sustainability benefits of establishing a food waste-based AD plant and upgradation of produced biogas to CBM to use it as a fuel for transit buses subsequently is not comprehensively understood for a city in developing nation.…”
Section: Introductionmentioning
confidence: 99%